Elements of classic choreography at the academization of Polish folk-stage dance - Shevchuk, Olha (Global Prosperity, 2023)
In this article the akademization of the Polish national and scenic dance is considered by creative elements of classical choreography. It is established that peculiar feature of the Polish folklore is organic association of music, singing and dances, in particular five the main of them - krakowiak, the polonaise, the mazourka, an oberek and a kuyavyak, and for each region of Poland special choreographic forms with own specific suits are characteristic. The lyricism, energy and elegance were characteristics of the Polish national and scenic choreography always. Approximately from 1840th years in Europe active process of an akademization of national and scenic dances begins. From the akademization Pole interest and in other folklore choreographic forms of the people of Eastern Europe, including Polish is connected. The polonaise which arose and gained the development on the basis of national and scenic dance gait was dance of the Polish people which passed through an akademization and became world famous. The mazourka was internationally recognized ball dance which gains distribution in the Czech Republic, Hungary, France and Russia in ХІХ century. Krakowiak appeared the Polish national dance, created in the Krakow voivodeship and over time turned into one of the most popular national dances of the Polish people.